Application of Zhuang medicine ironing therapy and external application in early functional rehabilitation of patients after anterior cruciate ligament reconstruction (壮医药熨联合壮医敷贴治疗在前交叉韧带重建术后患者早期功能康复中的应用效果) - HUANG Biqiu (黄碧秋); MO Lilu (莫理璐); LAN Yanglu (蓝阳露); ZHAO Xiangyue (赵香越) (Association of Integrative Nursing, 2023)
Objective To explore the effect of Zhuang medicine ironing therapy combined with Zhuang medicine external application in the early rehabilitation of patients after anterior cruciate ligament reconstruction. Methods Totally100 patients who underwent arthroscopic anterior cruciate ligament reconstruction were selected as the study subjects. All patients underwent arthroscopic single-bundle reconstruction with autogenous semitendinosus tendon and gracilis tendon. They were randomly divided into observation group and control group, with 50 cases in each group. The patients in the control group were given routine training combined with Zhuang medicine ironing therapy; On the basis of the control group, the observation group was treated with Zhuang medicine external application. The pain, knee joint swelling and range of motion were observed from the 2nd, 5th and 7th day after operation, and effect of treatment was evaluated and compared between two groups. Results At the 7th day after operation , the score of Visual Analogue Scale (VAS) and degree of knee joint swelling in the observation group were lower than those in the control group, respectively(P＜0. 05). Better improvement of range of active knee flexion motion and knee extension motion were observed in the observation group compared with those in the control group at 7 days after operation(P＜0. 01). Conclusion Zhuang medicine ironing therapy and external application may effectively relieve knee pain, reduce swelling, improve the range of motion of knee joint after arthroscopic anterior cruciate ligament reconstruction. The combination treatment of Zhuang medicine is beneficial to the recovery of knee joint function. (目的 观察壮医药熨联合壮医敷贴治疗在前交叉韧带重建术后患者早期康复中的应用效果。方法 选取2022年1月-12月行关节镜下前交叉韧带重建术患者100例为研究对象, 分为观察组和对照组, 各50例, 对照组患者给予常规的训练联合壮医药熨方法; 观察组在对照组的基础上联合壮医敷贴治疗。观察两组干预后膝关节功能康复效果。分别于术后第2天、第5天和第7天观察膝关节疼痛、肿胀缓解情况, 比较两组干预前后膝关节主动屈伸活动范围改善情况, 评价干预效果。结果 术后第7天, 观察组VAS评分低于对照组, 膝关节肿胀度小于对照组, 差异有统计学意义(P＜0. 05); 术后第7天, 观察组膝关节主动屈曲范围及膝关节伸展范围改善幅度优于对照组, 差异有统计学意义(P＜0. 01)。结论 关节镜下前交叉韧带重建术后患者早期功能康复中应用壮医药熨联合壮医敷贴治疗, 能有效缓解膝关节疼痛, 减轻肿胀, 改善膝关节活动度, 有利于膝关节功能的恢复。)